Fungal Species Causing Canker and Wilt of Ficus carica and Evidence of Their Association by Bark Beetles in Italy - Gusella, Giorgio (Plant disease, 2024)
Field surveys conducted during 2021 and 2022 in Western Sicily, Italy, revealed the presence of common fig trees severely affected by trunk and crown root canker and bark cracking. Moreover, in conjunction with the symptomatic tissues, the same surveyed plants showed the presence of bark beetle holes and internal wood galleries. The predominant beetle Criphalus dilutus was previously reported attacking figs in Sicily. Phylogenetic analyses based on multilocus DNA data showed the presence of different fungal taxa associated with disease symptoms, including Botryosphaeria dothidea, Ceratocystis ficicola, Diaporthe foeniculina, Neocosmospora bostrycoides, N. perseae, and Neofusicoccum luteum. Pathogenicity tests conducted on potted fig plants showed that all the species were pathogenic to fig, with C. ficicola and Neocosmospora spp. as the most aggressive fungal species. Moreover, isolations conducted from the bodies of emerging adult insects recovered from disease samples confirmed the presence of C. ficicola and Neocosmospora spp., suggesting the potential involvement of C. dilutus in their dissemination